2001
DOI: 10.2466/pr0.88.3.759-767
|View full text |Cite
|
Sign up to set email alerts
|

Stress, Coping, and Success Among Graduate Students in Clinical Psychology

Abstract: Research has indicated that coping styles and social support are moderating variables in the relationship between stress and distress. Few studies, however, have examined the relationship between these variables and the relative health and success of graduate students in clinical psychology. We administered measures of stress, psychological health, social support, and coping styles to 53 doctoral students in clinical psychology. Current grade point averages were used as a measure of academic success. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 13 publications
3
36
0
1
Order By: Relevance
“…A total score of more than 23 (range: 4-28, Cronbach's a=0,84) implies extreme fatigue for a student population (13). Time pressure was investigated with three items, one item about the perception of time pressure in general (yes/no), one item about time pressure related to the study (yes/no), and one item about experiencing difficulties to relax (1)(2)(3)(4)(5). Support was measured by contacts with professional caregivers and the wish for more social support from family and friends.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…A total score of more than 23 (range: 4-28, Cronbach's a=0,84) implies extreme fatigue for a student population (13). Time pressure was investigated with three items, one item about the perception of time pressure in general (yes/no), one item about time pressure related to the study (yes/no), and one item about experiencing difficulties to relax (1)(2)(3)(4)(5). Support was measured by contacts with professional caregivers and the wish for more social support from family and friends.…”
Section: Questionnairementioning
confidence: 99%
“…Such studies, however, have focused on students following a particular course only (4)(5)(6)(7)(8)(9) or only on psychological indicators of health (4,10). Early detection is possible only when the determinants of this health-related drop out are known.…”
Section: Introductionmentioning
confidence: 99%
“…Graduate students from nonnursing health science programs report similar sources of perceived stress. Academic expectations are a documented source of stress for pharmacy, psychology, and medical students as well as physician assistants and athletic trainers (Beall, DeHart, Riggs, & Hensley, ; Finkelstein, Brownstein, Scott, & Lan, ; Ford, Olotu, Thach, Roberts, & Davis, ; Heins, Fahey, & Leiden, ; Kuhn, Kranz, Koo, Cossio, & Lund, ; Marshall, Allison, Nykamp, & Lanke, ; Nelson, Dell'Oliver, Koch, & Buckler, ; Reed & Giacobbi, ). Several studies have found financial obligations as a source of stress for all students except athletic trainers (Beall et al., ; Finkelstein et al., ; Ford et al., ; Heins et al., ; Kuhn et al., ; Marshall et al., ; Nelson et al., ), whereas time management was perceived as stressful by all students except pharmacy students (Finkelstein et al., ; Heins et al., ; Kuhn et al., ; Nelson et al., ; Reed & Giacobbi, ).…”
Section: Introductionmentioning
confidence: 99%
“…A source of stress common to pharmacy and medical students included relationships (Beall et al., ; Finkelstein et al., ; Ford et al., ; Heins et al., ; Marshall et al., ), whereas psychology students found clinical practicum and working with clients to be stressful (Nelson et al., ). Athletic trainers reported uncertainty regarding the future as a source of stress (Reed & Giacobbi, ) illustrating the variety of sources of stress.…”
Section: Introductionmentioning
confidence: 99%
“…Morton and Worthley (1995) stated that the more hours of internship/externship the student completes, the greater their stress and lower their satisfaction with their program. Nelson, et al (2001) further explored the coping strategies associated with successful graduate students. Their findings indicate that successful psychology graduate students use less denial coping, and more religious, venting, and emotional/social support coping.…”
mentioning
confidence: 99%